PERLINDUNGAN KONSUMEN BROKER ASURANSI MENGHADAPI KETENTUAN MODAL MINIMUM PERUSAHAAN 2026 - Robidi, Robidi; Subrata, Agus; Ihsan, Muhamad; Kiatin, Desi Roro (JURNAL LENTERA BISNIS, 2026)
The minimum capital requirement for insurance companies planned to be implemented in 2026 constitutes a key element of prudential regulatory reform aimed at strengthening solvency and ensuring the stability of the insurance industry. However, this policy may generate indirect yet significant implications for consumer protection mechanisms, particularly through the role of insurance brokers as independent intermediaries. This study aims to comprehensively analyze the impact of the 2026 minimum capital requirement on consumer protection as exercised through insurance brokers, while linking regulatory developments to brokers’ empirical performance conditions during the 2023–2025 period. The research employs a qualitative approach using a juridical-empirical and policy analysis framework, drawing on regulatory documents and high-quality international academic literature. The findings indicate that stricter capital requirements tend to accelerate market consolidation and narrow brokers’ operational space in product comparison, policy negotiation, and consumer assistance. Such structural pressures may weaken brokers’ substantive independence and diminish their effectiveness as consumer protection instruments. The study concludes that consumer protection in the insurance sector cannot rely solely on insurers’ financial strength but must also be supported by a regulatory framework that preserves and strengthens the role of insurance brokers through proportional and risk-based regulatory approaches.